The challenges of implementing halal assurance practices in an organic halal-certified slaughterhouse at Negeri Sembilan - Al-Azmi, Ahmad Al-Ihsan; Hamid, Anis Hamizah (Universiti Teknologi MARA (UiTM), Malaysia, 2025)
The primary purpose of Halal Assurance practices is to support an industry that upholds Islamic morality and ethical standards, guaranteeing that consumers are receiving not only permissible but also safe and healthy food. This study explores the difficulties faced by a Halal-Certified slaughterhouse for organic chicken located at Nilai, Negeri Sembilan to face the world explosive growth of halal market. The study names financial limitation, challenges in recruiting expert personnel in managing halal slaughtering process and product traceability concerns as the main roadblocks. Through qualitative interviews with the Internal halal committee members, this study identifies key obstacles to upholding halal standards, including insufficient funding for training and equipment and labour-intensive manual traceability systems. The study also found the strategic solutions by Delima Emas, such as streamlining operations, improving training programs and upgrading traceability systems with digital recordkeeping and advanced analytics.